Seasonal Asymmetry in the Evolution of Surface Ocean pCO2 and pH Thermodynamic Drivers and the Influence on Sea‐Air CO2 Flux. Issue 10 (11th October 2018) - Fassbender, Andrea J.; Rodgers, Keith B.; Palevsky, Hilary I.; Sabine, Christopher L.
Abstract: It has become clear that anthropogenic carbon invasion into the surface ocean drives changes in the seasonal cycles of carbon dioxide partial pressure ( p CO2 ) and pH. However, it is not yet known whether the resulting sea‐air CO2 fluxes are symmetric in their seasonal expression. Here we consider a novel application of observational constraints and modeling inferences to test the hypothesis that changes in the ocean's Revelle factor facilitate a seasonally asymmetric response in p CO2 and the sea‐air CO2 flux. We use an analytical framework that builds on observed sea surface p CO2 variability for the modern era and incorporates transient dissolved inorganic carbon concentrations from an Earth system model. Our findings reveal asymmetric amplification of p CO2 and pH seasonal cycles by a factor of two (or more) above preindustrial levels under Representative Concentration Pathway 8.5. These changes are significantly larger than observed modes of interannual variability and are relevant to climate feedbacks associated with Revelle factor perturbations. Notably, this response occurs in the absence of changes to the seasonal cycle amplitudes of dissolved inorganic carbon, total alkalinity, salinity, and temperature, indicating that significant alteration of surface p CO2 can occur without modifying the physical or biological ocean state. This result challenges the historical paradigm that if the same amount of carbon and nutrients is entrained and subsequently exported, there is no impact on anthropogenic carbon uptake. Anticipation of seasonal asymmetries in the sea surface p CO2 and CO2 flux response to ocean carbon uptake over the 21st century may have important implications for carbon cycle feedbacks. Plain Language Summary: The ocean uptake of human released carbon dioxide (CO2 ) is causing the natural seasonal swings in seawater CO2 to grow over time. Using observations and numerical models, we conduct a theoretical experiment to see how the surface ocean may respond to continued carbon additions under "business‐as‐usual" future atmospheric CO2 concentrations. We find that between 1861 and 2100, the chemical properties of CO2 in seawater cause the seasonal CO2 maximum to grow by more than the seasonal CO2 minimum. As a result, the rate of summer surface ocean CO2 growth is different than winter, requiring year‐round observations to accurately measure the overall annual ocean carbon absorption. Additionally, these seasonal CO2 changes affect how much carbon is lost from the ocean during high‐CO2 periods relative to how much carbon is gained from the atmosphere during low‐CO2 periods, creating a trend in the average ocean carbon absorption over years to decades that must be considered in the interpretation of marine carbon cycle observations and numerical models. These findings are important as they have implications for future rates of climate change and ocean acidification. Key Points: Asymmetric amplification of surface ocean p CO2 and pH seasonal cycles is anticipated over the 21st century under RCP8.5 Expected seasonal asymmetries highlight ongoing challenges with using a summer‐biased observing network to estimate anthropogenic trends Projecting onto Revelle factor perturbations, the p CO2 seasonal cycle response may have important implications for carbon cycle feedbacks